Model of traditional market as cultural product outlet and tourism destination in current era - Aliyah, Istijabatul; Yudana, Galing; Sugiarti, Rara (Journal of Architecture and Urbanism, 2020)
The phenomenon occurring along with traditional market development is the safety aspect, criminal activities, the low hospitality in serving buyers, the lack of honesty in trade, excessive price range in bargaining, and the lack of product information. This study aims to formulate model of traditional markets as cultural product outlet and tourism destination in the current era. It was a descriptive study with a qualitative approach. Its location is Pasar Klewer, Surakarta District with considering textile commodity specification of cultural production result of low-class economy communities with the scale of South-East Asia service.  The study began with the explorations of potential, problems, effort and service of traditional markets, and government policy and commitment. Data were obtained through spatial and aspatial identification, site observation, in-depth interview, and document study. Sampling techniques were purposive and snowball sampling techniques. Furthermore, data analysis was carried out by using analytical methods, including 1) External and Internal Factors Analysis Summaries to analyze potential, problems, effort and service of traditional markets, and 2) Interactive Analysis to analyze the relevance of policy, commitment and effort carried out by traditional market actors. The result shows that traditional markets are one of tourism destination with historical values as outlets of community cultural products and populist economic spaces based on human source capabilities. The benefit of this study is directly received by market actors, policymakers of Surakarta Government, community and tourists, as well as academicians in scientific development in relation to cultural-art and tourism development based on the populist economy.